NGlycolylGM3/VSSP Vaccine in Metastatic Breast Cancer Patients: Results of Phase I/IIa Clinical Trial - de la Torre, Ana (Libertas Academica, 2012)
Patients treated with vaccines based on NGlycolil gangliosides have showed benefit in progression free survival and overall survival. These molecules, which have been observed in breast cancer cells, are minimally or not expressed in normal human tissue and have been considered as antigen tumor-specific. For this reason they are very attractive to immunotherapy. A phase I/II clinical trial was carried out in metastatic breast cancer patients with the NGlycolylGM3/VSSP vaccine administered by subcutaneous route. Selecting the optimal biological doses of the vaccine in these patients was the principal objective based on the immunogenicity, efficacy and safety results. Six levels of doses of vaccine were studied. Treatment schedule consisted of five doses every two weeks and then monthly until reaching a fifteenth doses. Doses levels studied were 150, 300, 600, 900, 1200 and 1500 μg. Five patients in each level were included except at the 900 μg dose, in which ten patients were included. Immunogenicity was determined by levels of antibodies generated in patients after vaccination. The response criteria of evaluation in solid tumors (RECIST) was used to evaluate antitumoral effect. Safety was evaluated by Common Toxicity Criteria of Adverse Event (CTCAE). The vaccine administration was safe and immunogenic in all does levels. Most frequent adverse events related to vaccination were mild or moderate and were related to injection site reactions and “flu-like” symptoms. Vaccination induced specific anti-NeuGcGM3 IgM and IgG antibodies responses in all patients. Disease control (objective response or stable disease) was obtained in 72.7% of evaluated patients. Median overall survival was 15.9 months. Two patients of two different dose levels achieved overall survival values of about six years. The dose of 900 μg was selected as biological optimal dose in which overall survival was 28.5 months.